Cardiac Fas Receptor-dependent Apoptotic Pathway in Obese Zucker Rats - Lee, Shin-Da; Tzang, Bor-Show; Kuo, Wei-Wen; Lin, Yueh-Min; Yang, Ai-Lan; Chen, Szu-Hua; Tsai, Fuu-Jen; Wu, Fong-Li; Lu, Min-Chi; Huang, Chih-Yang (Obesity research, 2007)
OBJECTIVE: Very limited information regarding the cardiac molecular mechanism in obesity is available. The purpose of this study was to evaluate the cardiac Fas receptor-dependent (type I) apoptotic pathway in obese Zucker rats. RESEARCH METHODS AND PROCEDURES: Sixteen obese Zucker rats were studied at 5 to 6 months of age, and 16 age-matched lean Zucker rats served as controls. Heart weight index, myocardial architecture, key components of the Fas receptor-dependent apoptotic pathway, apoptotic activity, and fibrosis in the excised left ventricle of rats were measured by weight scales, hematoxylin and eosin staining, Western blotting, TUNEL assay, and Masson trichrome staining. RESULTS: Body weight, whole heart weight, left ventricular weight, ratio of whole heart weight to tibia length, percentage of TUNEL-positive cardiac myocytes, and percentage of cardiac fibrosis were significantly increased in the obese group. Cardiomyocyte disarray and increased cardiac interstitial space were observed in obese rats. Protein levels of Fas ligand, Fas death receptors, and Fas-associated Death Domain were all significantly increased in the obese group. In addition, pro-caspase-8 and pro-caspase-3 were significantly decreased, whereas activated caspase-8 and activated caspase-3 were significantly increased in the obese group, which implies that pro-forms of caspase-8 and caspase-3 were cleaved into active-forms caspase-8 and caspase-3. CONCLUSIONS: Cardiac Fas receptor-dependent apoptotic pathways were more activated in obese rats' hearts, which may provide one of the possible apoptotic mechanisms for developing cardiac abnormality in obesity.